Pengembangan Media E-Booklet Berdasarkan Hasil Inventarisasi Tanaman Rempah di Kota Ternate sebagai Media Pembelajaran Biologi - Tabaika, Rosita; Udin, Asmita; Matdoan, Muhammad (Alpatih Harapan Semesta, 2025)
This study aims to develop an E-Booklet as a biology learning medium, based on the inventory of spice plants found in Tubo, Moya, and Jambula villages, intended for use at SMA Negeri 5 Kota Ternate. The research addresses the limited use of innovative media in classrooms and the underutilization of local biodiversity in education. Employing a modified Borg & Gall Research and Development (R&D) model, the study includes stages such as preliminary investigation, documentation of local spice plant species, E-Booklet design, expert validation, and limited trials with students. Data were collected using observation sheets, expert validation forms, and student learning assessments. The inventory identified a variety of spice plants, including ginger, turmeric, galangal, and nutmeg. Validation results from content and media experts indicated a high level of validity, with average scores exceeding 80%. Trial results demonstrated improved student understanding and interest in biodiversity topics. These findings suggest that the E-Booklet is both valid and effective for enhancing biology instruction. The research underscores the value of integrating local natural resources into educational materials to foster contextual learning and preserve indigenous knowledge. It also offers practical implications for educational policy and curriculum development that promote the inclusion of local wisdom in science education.